EFFECT OF WATER STRESS,LIGUD PARAFFIN AND CALCIUM CHLORIDE IN GROWTH,YIELD AND QUALITY IN POTATO - Zuhair A.Dawood (Mesopotamia Journal of Agriculture)
A field experiment was conducted in a private potato farm in Mosul City during two spring seasons of 2002 and 2003 , in sandy – loam soil . Liquid paraffin as anti transparent at two concentration ( 0 and 2 % ) were applied twice ( after 53 and 84 ) days from planting , and calcium chloride ( Ca Cl2 ) at three concentration ( 0,1 and 2 % ) were also applied twice ( 47 and 77 ) days from planting , respectively , to improve growth and yield of potato (Solanum tuberosum L . CV .Desiree ) , and to reduce the damage of water stress . Plants were exposured to water stress twice by no water supply till plant wilting during tubers formation period ( 51 and 82 days after planting date ) . The study included 12 treatments laid out in Factorial Experiment within Split – Plot Design replicated three times .The results can be summarized as follows: Exposuring potato plants to water stress caused a significant decreases in total water content (TWC) in leaves , leaf area , dry weight of plant , tuber number per plant , tuber weight , plant and marketable yield , and percentage of Ca content in tubers .However , a significant increases was observed in dry matter , percentage , total soluble solids (TSS) and percentage of loss and decayed tubers after storage . Foliar application of liquid paraffin at 2 % concentration significantly increased the TWC and total chlorophyll content in leaves , tubers number , tuber weight , plant and marketable tuber yield .While no significant effect were found on leaf area , plant dry weight and quantitative characters of tubers . Foliar application of calcium chloride by 1 and 2 % concentration , significantly increased the TWC in leaves , marketable yield , and Ca percentage in tubers. A significant decrease was shown in the percentage of loss and decay in stored tubers .The interaction treatments between liquid paraffin and CaCl2 , significantly decreased the damage effects of water stress on stressed plants and improved growth and yield of unstressed plants , however, the spraying of liquid paraffin and CaCl2 decreased the differences between water stressed and non-water stressed plants in many growth and yield characters .